2012
DOI: 10.5327/z0375-75362012000500003
|View full text |Cite
|
Sign up to set email alerts
|

Compartimentação geomorfológica e processos deposicionais no megaleque fluvial do rio São Lourenço, Pantanal mato-grossense

Abstract: ResumoA planície sedimentar do Pantanal é um extenso trato deposicional moderno, no qual megaleques fluviais são as feições que mais se destacam, sendo o do rio Taquari o maior e mais conhecido. Também notável é o megaleque do rio São Lourenço, que, apesar de possuir área de cerca de 16.000 km², é ainda pouco conhecido nos seus aspectos geológicos e geomorfológicos. Situado na borda noroeste do Pantanal, o megaleque do São Lourenço coalesce com o do Taquari, sendo dele separado pela planície fluvial interleque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This erosive intensity can alternate according to the climatic and hydropedological conditions in different epochs. However, comparing the dates with the environmental variations described by Corradini and Assine (2012) and by McGlue et al (2012), it can be observed that these profiles passed through a drier period with higher sedimentation that were favorable to concentration of ions in the soil and the formation of saline and sodic characters. Because the current climate conditions are more humid, the incision of the rivers is more accentuated and, consequently, erosion processes predominate, which are the main aspect 5000 μm 5000 μm 5000 μm 1000 μm Figure 7.…”
Section: Soil Properties and Pedogenetic Processesmentioning
confidence: 99%
“…This erosive intensity can alternate according to the climatic and hydropedological conditions in different epochs. However, comparing the dates with the environmental variations described by Corradini and Assine (2012) and by McGlue et al (2012), it can be observed that these profiles passed through a drier period with higher sedimentation that were favorable to concentration of ions in the soil and the formation of saline and sodic characters. Because the current climate conditions are more humid, the incision of the rivers is more accentuated and, consequently, erosion processes predominate, which are the main aspect 5000 μm 5000 μm 5000 μm 1000 μm Figure 7.…”
Section: Soil Properties and Pedogenetic Processesmentioning
confidence: 99%